P311 Reliability of computed tomography enterography for evaluation of stricturing Crohn's disease: Development of a Crohn's disease stricture index. (30th January 2023) - Rieder, F; Ma, C; Hanzel, J; Fletcher, J G; Baker, M; Wang, Z; Guizetti, L; Patel, M; Niu, J; Shackelton, L; Ottichilo, R; Santillan, C; et al.
Abstract: Background: Computed tomography enterography (CTE) is frequently used to assess stricturing Crohn's disease (CD). However, the reliability of CTE items used for assessment has not been established and there is no validated radiologic stricture severity index. Methods: We conducted a retrospective study of 43 patients with symptomatic, terminal ileal stricturing CD. Four radiologists assessed a comprehensive list of pre-defined radiologic items potentially associated with stricture severity in 48 CTE scans in two separate rounds in random order. Reliability was quantified using the intraclass correlation coefficient (ICC). Items with at least moderate (ICC≥0.41) inter-rater reliability that were correlated with a visual analogue scale of overall stricture severity were candidate items for the development of a CTE stricture index. Results: Inter-rater reliability was almost perfect for assessment of luminal diameter of pre-stenotic dilation (ICC 0.817 [95% confidence interval 0.703, 0.878]), substantial for stricture length (ICC 0.628 [0.419, 0.797]), and moderate for stricture wall thickness (0.482 [0.330, 0.601]). Intra-rater reliability was almost perfect (ICC ≥ 0.850) for all three items. A stricture severity index was derived and was well calibrated (optimism-adjusted calibration slope = 1.009), with scores calculated as the sum of stricture length (cm) + luminal diameter of pre-stenotic dilation (mm) + 5 x stricture wall thickness (mm). Conclusion: Stricture length, prestenotic dilation, and stricture wall thickness can be reliably assessed, and are component items for a novel CTE stricture index (CTE-SI) of stricture severity for CD-related terminal ileal strictures. Additional external index validation for clinical and research contexts is required.